Maintaining Healthy Skin During COVID-19 Pandemic - Venny Larasati; Soilia Fertilita (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The Covid-19 pandemic has brought several changes to people's routine habits. Educating the public about the importance of washing and disinfecting hands as often as possible and the use of personal protective equipment such as masks, googles or face shields to avoid disease transmission and sunbathing habits to get the benefits of sunlight for health and the immune system has an impact on behavior changes on the community. These new habits can bring a negative effect to the skin. The use of disinfectants and personal protective equipment can cause allergic dermatitis, contact dermatitis, skin maceration, secondary fungal infection and acne. Sunbathing can cause changes in skin pigmentation, the appearance of black spots, the skin looks dull and rough and accelerates the appearance of premature wrinkles on the skin. Proper skin care routine during this pandemic situation is essential to maintain skin healthy and avoid skin problems due to the use of disinfectants or PPE. The use of emollients, moisturizers and barrier creams can prevent skin problems to happen. Skin moisturizers can be used regularly after hand washing and before using personal protective equipment. When it comes to maintaining healthy skin during pandemic, skin care routine consists of facial cleansers, toners, moisturizers, serums, morning creams and night creams are also recommended to keep the skin healthy and slow the appearance of premature aging signs on the skin. This activity aims to provide a better understanding to people especially worker how to prevent skin problems and how to maintain healthy skin during pandemic.